LEARNING POETRY AS A STRATEGY TO DEVELOP TEACHING SKILL AMONG STUDENTS - Mulatsih, Maria Ika (Sanata Dharma University Yogyakarta, 2018)
Generally, learning poetry has some functions which deal with oral language development, student learning style expansion, world engagement with its content, and cultural awareness exploration. The fact is that not only does Indonesia government try to put aside learning literature from all language study programs, but also some practitioners argue that there is no link between learning poetry and developing students’ teaching skill in some teachers training departments. This article argues that learning poetry can be a medium to develop students’ teaching skill in sharing the knowledge independently and creatively. Some practices that have been conducted in two poetry classes of English Language Education Program, Sanata Dharma University in 2017 are being discussed in relation to improve students’ teaching skill as preliminary activities before having a micro teaching class. Additional data about students’ response toward the practices are also shown. It was found that 82% students agreed that those practices developed students’ teaching skill in sharing the knowledge that they got. DOI: https://doi.org/10.24071/ijiet.2018.020203